Alpha-SNAP Enhances SNARE Zippering by Stabilizing the SNARE Four-Helix Bundle - Ma, Lu (Cell Rep, 2016)
Intracellular membrane fusion is mediated by dynamic assembly and disassembly of soluble N-ethylmaleimide-sensitive factor (NSF) attachment protein (SNAP) receptors (SNAREs). α-SNAP guides NSF to disassemble SNARE complexes after membrane fusion. Recent experiments showed that α-SNAP also dramatically enhances SNARE assembly and membrane fusion. How α-SNAP plays roles in these opposing activities is not known. Here, we examined the effect of α-SNAP on the step-wise assembly of the synaptic SNARE complex using optical tweezers. We found that α-SNAP destabilized the linker domain (LD) of the SNARE complex but stabilized its C-terminal domain (CTD) through a conformational selection mechanism. In contrast, α-SNAP minimally affected assembly of the SNARE N-terminal domain (NTD), indicating that α-SNAP barely bound the partially assembled trans-SNARE complex. Thus, α-SNAP recognizes the folded CTD for SNARE disassembly with NSF and subtly modulates membrane fusion by altering the stabilities of the SNARE CTD and LD.